2017
DOI: 10.3389/fimmu.2017.00641
|View full text |Cite
|
Sign up to set email alerts
|

Belatacept Does Not Inhibit Follicular T Cell-Dependent B-Cell Differentiation in Kidney Transplantation

Abstract: Humoral alloreactivity has been recognized as a common cause of kidney transplant dysfunction. B-cell activation, differentiation, and antibody production are dependent on IL-21+CXCR5+follicular T-helper (Tfh) cells. Here, we studied whether belatacept, an inhibitor of the costimulatory CD28-CD80/86-pathway, interrupts the crosstalk between Tfh- and B-cells more efficiently than the calcineurin inhibitor tacrolimus. The suppressive effects of belatacept and tacrolimus on donor antigen-driven Tfh–B-cell interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 57 publications
(71 reference statements)
0
28
0
Order By: Relevance
“…A recent study from our group demonstrated that Tac had a small inhibitory effect on Tfh-cell generation in vitro and could partially prevent Tfh-cell activation. The production of IL-21 was incompletely inhibited by high concentrations of Tac, which may be why the remaining activated Tfh cells retained the potential capacity to assist B cells ( 60 ). In another study, methylprednisolone treatment of patients with systemic lupus erythematosus was found to reduce the number of peripheral CD4 + CXCR5 + PD-1 + T cells, but without any evidence of altered Tfh function ( 61 ).…”
Section: The Effects Of Conventional Immunosuppression On Tfh Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study from our group demonstrated that Tac had a small inhibitory effect on Tfh-cell generation in vitro and could partially prevent Tfh-cell activation. The production of IL-21 was incompletely inhibited by high concentrations of Tac, which may be why the remaining activated Tfh cells retained the potential capacity to assist B cells ( 60 ). In another study, methylprednisolone treatment of patients with systemic lupus erythematosus was found to reduce the number of peripheral CD4 + CXCR5 + PD-1 + T cells, but without any evidence of altered Tfh function ( 61 ).…”
Section: The Effects Of Conventional Immunosuppression On Tfh Cellsmentioning
confidence: 99%
“…In kidney transplant patients, we found that belatacept partially inhibited Tfh-cell activation; the remaining activated Tfh cells were able to provide B cell help. Belatacept is less potent in vitro than Tac in inhibiting Tfh-cell-dependent plasmablast formation ( 60 ). Based on these preliminary data, it seems that human circulating Tfh cells after transplantation are less susceptible to costimulation blockade than mouse Tfh cells.…”
Section: Tfh-targeted Immunotherapymentioning
confidence: 99%
“…Disrupting this process could be key to developing more effective therapies for AMR. The recent study by de Graav et al describes the effects of belatacept and tacrolimus on the process of Tfh cell–dependent B-cell differentiation ( 1 ). Their data provide important insights into the isolated effects of tacrolimus and belatacept in vitro , but do not demonstrate that belatacept fails to inhibit Tfh cell-dependent B-cell differentiation in kidney transplantation, as the article title suggests.…”
mentioning
confidence: 99%
“…[97][98][99] However, it was initially unclear as to whether belatacept was functioning directly on B cells or through a secondary impact on Tfh cells. [97][98][99] However, it was initially unclear as to whether belatacept was functioning directly on B cells or through a secondary impact on Tfh cells.…”
Section: Belatacept Therapy Can Inhibit Memory T Follicular Helpermentioning
confidence: 99%
“…Belatacept has been shown to be effective at abolishing germinal centers and mitigating alloantibody responses in allosensitized patients. [97][98][99] However, it was initially unclear as to whether belatacept was functioning directly on B cells or through a secondary impact on Tfh cells. 100 In an evaluation of peripheral circulating Tfh cells, belatacept therapy was shown to be on par with traditional calcineurin inhibition in mitigating influence of Tfh on B-cell differentiation post-transplant.…”
Section: Belatacept Therapy Can Inhibit Memory T Follicular Helpermentioning
confidence: 99%